Implementation of Law Number 35 of 2014 concerning Child Protection in the Tarbiyatus Shibyan Putri Dormitory, Pesantren Attahdzib - Latifah, Hanik; Charisna Binti Rofidatul Izzah (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
This study examines the implementation of Law Number 35 of 2014 Article 9 Paragraph 1a concerning child protection in Pesantren Attahdzib, particularly at Tarbiyatus Shibyan Female Dormitory. The research focuses on how the pesantren enforces child protection against physical and verbal abuse through religious values and psychological approaches. The study employs a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. Key informants include coordinators, mentors, and students directly involved in the mentoring process. The findings reveal that mentoring in Pesantren Attahdzib integrates principles of compassion, discipline, and assertive communication in student management. Supporting factors include parental collaboration, a conducive pesantren environment, and mentors’ role modeling. However, challenges such as mentors’ lack of experience and suboptimal communication with guardians persist. In conclusion, the pesantren successfully fosters a safe educational environment that supports students’ spiritual, social, and psychological development in line with the law’s mandates.